Analysis of User Acceptance Levels Using the Unified Theory of Acceptance and Usage of Technology on Streaming Service and Video-On-Demand Channels Customers - Yuni Dharta, Firdaus; Violin, Vivid; Wahyono, Teguh; Wirabuana Putra, Gede (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to use the UTAUT model to examine the variables that affect consumers' adoption of streaming applications. Surveys were employed to gather data for the study, which took a quantitative approach. The study sample comprises individuals who use streaming applications in select Indonesian cities. A purposive sampling strategy was used in this study, with a sample size of one hundred participants. For data analysis, researchers used statistical data processing tools. This study processed demographic data using Microsoft Excel, wrote reports using Microsoft Word, and performed statistical analysis using the PLS-SEM approach with SmartPLS. According to the study's findings, users' opinions on streaming apps are moderately influenced by the factors in the UTAUT 2 model, which also explains half of the difference in users' usage intensity. As per the accepted hypothesis, several factors influence behavioral intention: performance expectation, facilitating conditions, price value, habit, hedonic motivation, behavioral intention on use behavior, and behavioral intention on use behavior. Hedonic motivation, price value, performance expectation, facilitating conditions, and habits affect behavioral intention; conversely, promoting conditions, habits, and use of behavior influence behavioral intention.